Thomas Jefferson's education - Taylor, Alan, 1955- (W.W. Norton & Company, 2019)
"From the Pulitzer Prize- winning historian, a brilliant, absorbing study of Jefferson and his campaign to save Virginia through education. By turns entertaining and tragic, this beautifully crafted history reveals the origins of a great university in the dilemmas of Virginia slavery. Thomas Jefferson shares center stage with his family and fellow planters, all dependent on the labor of enslaved black families. With a declining Virginia yielding to commercially vibrant northern states, Jefferson in 1819 proposed to build a university to educate and improve the sons of the planter elite. They, he hoped, might one day lead a revitalized Virginia free of slavery-- and free of the former slaves. Jefferson's campaign to build the university was a contest for the future of a state and the larger nation. Although he prevails, Jefferson's vision of reform through education is hobbled by the actions of genteel students whose defiant sense of honor derived from owning slaves. It is the women of this hypermasculine society-- particularly Jefferson's granddaughters--who redeem the best elements of his legacy"--